2006
DOI: 10.1139/h06-008
|View full text |Cite
|
Sign up to set email alerts
|

Soleus muscle force following downhill running in ovariectomized rats treated with estrogen

Abstract: The ovariectomized (OVX) rat model was used to investigate the effects of estrogen treatment on soleus muscle functionality in situ following muscle injury induced by downhill running. Fifty immature, 24- to 26-d-old, OVX rats were randomly assigned to 5 separate experimental groups: sedentary controls (OVX-Sed), placebo-treated and studied immediately after exercise (OVX-Pb0), placebo-treated and studied 72 h after exercise (OVX-Pb72), estradiol-treated and studied immediately after exercise (OVX-Ed0), and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
(64 reference statements)
3
11
0
Order By: Relevance
“…Indeed, E2 deficient muscles with significantly lower force/ unit area demonstrated rescue of muscle force when E2 was given back to rats that were OVX (Moran et al 2006(Moran et al , 2007. Our findings and those of others support the possibility that E2, rather than T2 or progesterone, aided rehabilitation efforts in this study (Enns and Tiidus 2008;Koot et al 1991;Sotiriadou et al 2006;Enns and Tiidus 2008;Trenkle 1976). McClung et al (2006) reported that loss of ovarian hormones impaired the recovery of fiber CSA in the atrophic SOL following 2 weeks of HLU.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Indeed, E2 deficient muscles with significantly lower force/ unit area demonstrated rescue of muscle force when E2 was given back to rats that were OVX (Moran et al 2006(Moran et al , 2007. Our findings and those of others support the possibility that E2, rather than T2 or progesterone, aided rehabilitation efforts in this study (Enns and Tiidus 2008;Koot et al 1991;Sotiriadou et al 2006;Enns and Tiidus 2008;Trenkle 1976). McClung et al (2006) reported that loss of ovarian hormones impaired the recovery of fiber CSA in the atrophic SOL following 2 weeks of HLU.…”
Section: Discussionsupporting
confidence: 80%
“…We did not measure progesterone but findings from other studies strongly suggest that recovery of injured muscle occurs independently of progesterone (Enns and Tiidus 2008;Koot et al 1991;Sotiriadou et al 2006). Only testosterone was measured in this study and if T2 is a reflection of progesterone levels, neither recovery group benefitted from its potential anabolic effect.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…After exercise, the animals of the Pb-Ex48 and VE-Ex48 groups were placed back in their cages with free access to food and water until they were examined. The exercise protocol implemented in this study has been widely used in previous studies and induced injury in the soleus and other rat hindlimb muscles (Armstrong et al 1983;Ogilvie et al 1988;Sotiriadou et al 2006;Takekura et al 2001). This study focused on the soleus, because it had been reported that downhill running induced more muscle injury to the soleus than other muscles in previous studies (Armstrong et al 1983;Lynch et al 1997;Smith et al 1997).…”
Section: Exercise Protocolmentioning
confidence: 99%
“…Additionally, E 2 acting via ERα is also shown to promote phosphorylation of p38 MAPK (Ronda et al, 2010a, 2010b), a signaling cascade shown to enhance GLUT4 intrinsic activity and glucose uptake (Furtado et al, 2002; Niu et al, 2003; Sweeney et al, 1999). Furthermore, it is possible that ERα activation of Akt and MAPK pathways may underlie in large part the E 2 -mediated protection of muscle against age-induced sarcopenia (Chen et al, 2005; Leger et al, 2008; Messier et al, 2011; Sipila et al, 2001; Sorensen et al, 2001; Teixeira et al, 2003; Tiidus, 2000), exercise-induced muscle damage (Dieli-Conwright et al, 2009; Sotiriadou et al, 2006; Thomas et al, 2010; Tiidus, 2000), and myocyte apoptosis in the face of a variety of cellular perturbations (Boland et al, 2008; McLoughlin et al, 2009; Vasconsuelo et al, 2008; Wang et al, 2010). Thus, ERα stimulation of muscle growth and insulin sensitivity via direct and indirect interaction with these pathways requires further exploration.…”
Section: Estrogen Action and Insulin Sensitivitymentioning
confidence: 99%